Unlocking the treasure trove: From genes to schizophrenia biology - CORVIN, AIDEN (My University, 2014)
Significant progress is being made in defining the genetic etiology of schizophrenia. As the list of implicated genes grows, parallel developments in gene editing technology provide new methods to investigate gene function in model systems. The confluence of these two research fields—gene discovery and functional biology—may offer novel insights into schizophrenia etiology. We review recent advances in these fields, consider the likely obstacles to progress, and consider strategies as to how these can be overcome.
PUBLISHED
Cited By :1 Export Date: 3 March 2015
Keywords: schizophrenia; schizophrenia